2016
DOI: 10.1186/s13195-016-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

ABT-126 monotherapy in mild-to-moderate Alzheimer’s dementia: randomized double-blind, placebo and active controlled adaptive trial and open-label extension

Abstract: BackgroundResults from a phase 2a study indicated that treatment with the novel α7 nicotinic acetylcholine receptor agonist ABT-126 25 mg once daily (QD) was associated with a trend for improvement in cognition in subjects with mild-to-moderate Alzheimer’s dementia (AD). A phase 2b program was designed to evaluate a broader dose range of ABT-126 as monotherapy in subjects with mild-to-moderate AD. The program consisted of a double-blind, placebo and active controlled study of ABT-126 (dose range 25–75 mg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 35 publications
(29 reference statements)
0
44
0
Order By: Relevance
“…Furthermore, according to docking calculations, curcuminoids glucuronide showed no obvious inhibitory effects against AD‐related acetylcholinesterase and β‐amyloid precursor cleavage enzyme (Shen et al, ). Acetylcholinesterase inhibitors are efficacious in improving cognitive function of mild‐to‐moderate AD (Gault et al, ). And pharmacological β‐amyloid precursor cleavage enzyme inhibition has found slow progressive β‐amyloid deposition and associated synaptic pathology in a transgenic AD model (Peters et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to docking calculations, curcuminoids glucuronide showed no obvious inhibitory effects against AD‐related acetylcholinesterase and β‐amyloid precursor cleavage enzyme (Shen et al, ). Acetylcholinesterase inhibitors are efficacious in improving cognitive function of mild‐to‐moderate AD (Gault et al, ). And pharmacological β‐amyloid precursor cleavage enzyme inhibition has found slow progressive β‐amyloid deposition and associated synaptic pathology in a transgenic AD model (Peters et al, ).…”
Section: Discussionmentioning
confidence: 99%
“… AD Phase II (terminated in 2014) K i : 12–14 nmol/L (in h α 7, r α 7 and m α 7) 93. , 94. (AbbVie) Schizophrenia Phase II (terminated in 2014) (AbbVie) AZD0328 Partial agonist Binding affinity: Mice: NOR in normal mice 96.…”
Section: α 7 Nachr Modulatorsmentioning
confidence: 99%
“…ABT-126 is a potent and selective a7 nAChR agonist with high binding affinity (K i = 12-14 nM) to a7 nAChRs (human, rat, or mouse cortex) (Gault et al, 2016). ABT-126 shows significantly less affinity (.140-fold) toward other nAChR subtypes and muscarinic receptor and therefore is expected to eliminate the dose-limiting toxicity associated with acetylcholine esterase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…ABT-126 was evaluated in single-dose and multiple dose phase 1 studies, and doses up to 150 mg once daily or up to 40 mg twice a day were generally well tolerated (AbbVie internal data). The results of a phase 2a trial indicated that treatment with ABT-126 was associated with a trend for improvement in cognition in subjects with mild to moderated AD (Gault et al, 2015); however, the subsequent phase 2b trial encompassing a broader dose range did not demonstrate statistically significant improvement versus a placebo control (Florian et al, 2016;Gault et al, 2016). In another phase 2a trial in subjects with schizophrenia, ABT-126 demonstrated a precognitive effect in nonsmoking subjects, particularly in verbal learning, working memory, and attention (Haig et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%